Perception of empowernment among international students in the Faculty of Educational Studies, University Putra Malaysia - Aloysius, Odigbo Ikechukwu; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Empowerment means enhancement of student's autonomy for decision making. Reports have shown that students who are empowered perform better, and have better relationship with the staff. Therefore this study was carried out to explore the experience of student’s empowerment at the Faculty of Educational Studies, Universiti Putra Malaysia. Informed by a phenomenological qualitative research design, analysis of various sources of primary data was carried out using semi-structured interviews with international students to understand their opinions and perceptions about empowerment in the Faculty of Educational Studies. Results obtained were analyzed, transcribed and discussed about their perception of empowerment and the effect on performance. The findings showed a sense of dis-empowerment among the informants as a result of a lack of motivation and problems with integration between the students and the staff. Student's reported that they can be empowered by allowing them more freedom in their studies. However, they recommend that management should assist in sensitizing local student's to feel free to socialize with international students for improved performance. Recommendation for enhancing empowerment among international students and directions for further research in this area are discussed.